Faktor-Faktor Yang Mempengaruhi Perilaku Konsumsi Mahasiswa Muslim dan non-Muslim terhadap Makanan Halal di Jatinangor Kabupaten Sumedang - Cupian, Cupian; Rahmah, Rahmah; Salsabila, Zahrah; Noven, Sarah Annisa (Jurnal Ilmiah Ekonomi Islam, 2024)
This journal examines the Factors Influencing the Consumption Behavior of Muslim and non-Muslim Students in Jatinangor. This study aims to describe whether the halal logo, the level of religiosity, food ingredients, and the manufacturing process have a significant effect on the decision to buy halal food. This study uses a quantitative approach with multiple linear regression methods. The objects studied were Muslim and non-Muslim students in Jatinangor with a sample size of 126 students. The result is that factors such as the halal logo, the level of religiosity, food ingredients, and the manufacturing process have a significant effect on the decision to buy halal food. This means that the more food products that use the halal logo, the higher one's religiosity, the more attention to food ingredients, and the more knowledge about the manufacturing process, the more students decide to buy halal food.